2013
DOI: 10.1155/2013/642362
|View full text |Cite
|
Sign up to set email alerts
|

Association of Seat Height and Arm Position on the Five Times Sit-to-Stand Test Times of Stroke Survivors

Abstract: Objectives. To investigate (1) the association of seat height and (2) the association of arm position on the five times sit-to-stand test (FTSTS) times of individuals with stroke. Design. A cross-sectional study. Setting. University-based rehabilitation centre. Subjects. Patients (n = 43) with chronic stroke. Methods. The times in completing the FTSTS with different seat height (85%, 100%, and 115% knee height) and arm positions (arms across chest, hands on thighs). Results. FTSTS times were significantly diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 50 publications
3
20
1
Order By: Relevance
“…Consistent with the results of previous studies with healthy individuals (25,(37)(38)(39) and those with functional limitations (40), our results also showed that there was no significant influence of arm position on FTSTS completion times.…”
Section: Arm Positions and Five Times Sit-to-stand Test Completion Timessupporting
confidence: 93%
“…Consistent with the results of previous studies with healthy individuals (25,(37)(38)(39) and those with functional limitations (40), our results also showed that there was no significant influence of arm position on FTSTS completion times.…”
Section: Arm Positions and Five Times Sit-to-stand Test Completion Timessupporting
confidence: 93%
“…Postural sway would increase due to balance impairment during sit-to-stand activity. On the other hand, in our study the extension phase was not present properly in 38% of stroke patients and 33% of older adults; in other study the risk of fall was greater and needed more time for stabilization especially during extension phase of sit- 17 to-stand activity.…”
Section: Falconcontrasting
confidence: 79%
“…Hence, it can be extracted that stroke affects the mobility of a person more than ageing and can increased various mobility related complications. another research sample with chronic stroke knee extensor weakness which takes greater time to rise during sit-tostand activity than normal individual 17 (elderly).…”
Section: Resultsmentioning
confidence: 99%
“…The findings of these authors were in agreement with some others who had measured performance variables of the STS task on dry land. One study showed that the five times sit-to-stand test were significantly longer using the lowest seat (85% knee height) compared with the other two heights, while no differences existed between the medium height and highest seat (100% and 115% knee height) (Ng, Cheung, Lai, Liu, Ieong, & Fong, 2013). Another study using a similar test (30-second chair stand test) studied the performance of community-dwelling older adults during the test at a standard height (43 cm) and from five seat heights (from 80% to 120% of each participant's lower leg length) showed that the mean score for standard conditions was significantly lower from higher chairs, but not significantly different between the standard and lower chairs (Kuo, 2013).…”
Section: Discussionmentioning
confidence: 99%